The English Translation of Qadyanism and Ideology: A Comparative Study of Shar Ali's Translation - Mahmoud Ibrahim Rezk Elnemr (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The research examines the influence of the theological ideology on The Holy Qur’an, 1997 by Shar Ali; moreover, it demonstrates the relationship between ideology and translation. conveyed and supported their beliefs through translations. The Qadyani translators of the Qur’an convey and support their beliefs through translations. They dedicate themselves to produce English translations which were circulated at a very wide scale with a missionary spirit in the English-speaking world with a view to win over unsuspecting readers to Qadyanism. The comparative method is used to explore the different aspects of ideology on the translation and exposes many results as shown in the current study. Sher Ali’s translation is prejudiced and influenced by the Qadiani beliefs. He misrepresents and mistranslates many verses that shall be scrutinized in the research. He depends on unauthentic beliefs which distorted the core of Islam and distorts the attributes of Allah. The translator denies the finality of the prophethood and denies the miracles of the prophets. The translation of several verses which refers to the theological ideology of Qadyanism movement. In translating verses on miracles, prophethood, and Jesus, for instance, these translations show their distinctiveness and how this sect distorted the Qur’anic text to present its beliefs and thoughts.